A study on the relationship between student entrepreneurship intentions using theory of planned behavior of final semester bachelor degree students at UiTM Pahang. / Norieziana Mohd Noh - Mohd Noh, Norieziana (Faculty of Business and Management, 2020)
This study examines the relationship between theory of planned behavior (TPB) and Entrepreneurship intention of final semester students of bachelor's degree at UiTM Pahang branch, Jengka campus. It also determines the TPB as independent variable which consist into three, Attitudes towards behavior, subjective norms and perceived behavior control. Entrepreneurship intention was determined as dependent variable. A total of 118 questionnaire were distributed to final semester students of bachelor's degree at UiTM Pahang. The questionnaire was divided into five section, which are section A to section E. Section A is a socio-demographic that consist five question. Second, the theory of planned behavior was in section B, C and D. Section B covered attitude toward behavior, section C the question on subjective norms and section D us perceived behavioral control. For the last section is section E, the question cover on entrepreneurship intention. The researcher conducted the study at UiTM, Pahang, Jengka. Questionnaires are distributed to students UiTM in order to collect the data for this finding. The researcher interprets the data received using Statiscal Package for the Social Science (SPSS). The objective of this study is to identify the level of student entrepreneurship intention between Theories of Planned Behavior. The study conducted to observe about relationship of Theory of Planned Behavior with entrepreneurship intention among student UiTM, Pahang. The result obtained was documented in depth through this report. The researcher also come up with several recommendation and suggestion for the future study.